Decoding the context of servitization: socio-technical pivots on the journey to service-oriented business models in manufacturing firms - Kurtz, Julian; Meyer, Patrick; Roth, Angela (Production Planning & Control, 2023)
Servitization has been discussed in academia and practice for decades, but there is still a lack of concrete guidance for manufacturing firms to orchestrate their servitization journeys. This study addresses this deficiency by analysing 88 annual reports of manufacturing firms. Using a multi-cycle inductive coding approach, six pivotal factors in servitization journeys were derived in order to decode their context. The pivotal factors represent fields of action in which manufacturing firms are currently active on their servitization journeys. They include both frontstage (e.g. market proposition) and backstage (e.g. process excellence) factors and predominantly emphasise technological over social activities. This exploratory study contributes to a more nuanced and contextualised understanding of the transformation of manufacturers into service-oriented firms. More importantly, this study sheds new light on servitization research by applying a socio-technical perspective and proposes a practical structuring of the servitization journey with tandems to navigate the journey.<br
Keywords: Servitization; business model innovation; product-service systems; socio-technical system perspective

Exploring Customers' Acceptance of and Resistance to Service Robots in Stationary Retail - a Mixed Method Approach - Meyer, Patrick; Jonas, Julia; Roth, Angela (ECIS 2020 Research Papers, 2020)
Stationary retailers continue to try to respond to customers’ needs with regard to service offering and quality. Consequently, they are attempting to develop innovative value propositions and co-create value with customers through new technologies. Among other technologies, service robots (SR) are said to have the potential to revitalise interactive value creation in stationary retail. Nonetheless, the integration of such technologies poses new challenges. Use cases are subject to research, but few studies have explored customers’ perceptions of SRs from a service systems’ perspective, though this is crucial to integrating SRs into stationary retail service systems. In this study, a mixed method approach is adopted to explore customers’ acceptance of and resistance to SRs. First, a qualitative exploratory interview study is conducted among 24 customers. Second, a qualitative survey and a quantitative questionnaire are carried out. The findings identify decisive drivers and barriers, i.a. ‘social presence’ and ‘role congruency’ and reveal i.a. that customers envision harmonious human-robot teams with transparent responsibilities that improve service interactions: while SRs assist frontline employees (FLE) and respond to simple customer inquiries, FLEs can dedicate more time engaging with customers and providing professional customer advice. Moreover, customers suggest that SRs be introduced gradually and with FLEs’ qualified assistance.<br
Keywords: service robots; service systems; customer interaction; human-robot interaction

Frontline employees’ acceptance of and resistance to service robots in stationary retail - an exploratory interview study - Meyer, Patrick; Jonas, Julia; Roth, Angela (19th Conference of the European Academy of Management (EURAM), 2019)

Frontline Employees' Acceptance of and Resistance to Service Robots in Stationary Retail - An Exploratory Interview Study - Meyer, Patrick; Jonas, Julia; Roth, Angela (Journal of Service Management Research, 2020)

Humanoide Serviceroboter am PoS: Eine akzeptanzanalytische Untersuchung neuer Formen der Kundeninteraktion - Meyer, Patrick; Spreer, Philipp; Gutknecht, Klaus (Marketing Review St. Gallen, 2018)
Servicerobotern wird großes Potenzial am PoS zugesprochen, Voraussetzung ist aber die Kundenakzeptanz. Die vorliegende Studie zeigt, dass diese massgeblich von der Interaktionsqualität, dem wahrgenommenen Nutzen und – überraschenderweise – vor allem dem wahrgenommenen Spass an der Interaktion mit einem Serviceroboter determiniert wird.<br
Keywords: Service Robots; Service Systems; Technology Acceptance; Retail Innovation

Innovation process design for servitisation: the digital service innovation case at uvex - Kurtz, Julian; Meyer, Patrick; Lugmair, Nina; Ries, Lena; Roth, Angela (Journal of Enterprise Information Management, 2025)
Purpose: The purpose of this study was to increase knowledge of digital service innovation in servitisation by extending design principles and proposing an innovation process design for smart product-service systems (PSS) development. Furthermore, the study addresses the alignment of multiple stakeholders in the development of smart PSS, thereby bridging the gap between theory and practice. Design/methodology/approach: A qualitative 17-month action design research approach was taken. This study designed an innovation process for smart PSS development. For this, different development streams were synchronised and multiple stakeholder perspectives were integrated. Drawing on the socio-technical systems perspective as theoretical lens, the authors utilised knowledge in the field of digital service innovation and servitisation. In multiple iterations, the authors, together with practitioners, explored how best to synchronise different smart PSS development activities to ensure subsequent operations of the system. Findings: The findings of the longitudinal study conducted with the manufacturing firm uvex propose a hybrid stage-gate innovation process design for smart PSS development. An evaluation with several international academics and practitioners enhances the rigour of the innovative approach. Originality/value: The findings contribute to the literature on digital service innovation and servitisation by applying a rarely used socio-technical perspective to innovation process design for smart PSS development. The longitudinal approach over 17 months in a qualitative action design research setting adds to the knowledge base with novel insights from practitioners’ problems.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Action design research; Digital service innovation; Innovation process design; Product-service systems; Servitization; Socio-technical systems

Managing Robotics in Retail: A Service Systems Perspective - Meyer, Patrick (WI 2020: DOCTORAL CONSORTIUM, 2020)
Due to rising online competition, increasing cost pressure and cross-channel customer journeys, stationary retail has tried to co-create value with customers through new technologies, which are expected to profoundly change stationary retail systems. One such technology, service robots, is said to rapidly change how value is created in organisational frontlines. However, the integration of this technology poses new challenges, as service robots interact with multiple stakeholders within a retail system. Consequently, it is crucial for service organisations to deeply understand how customers and frontline employees (FLEs) perceive service robots in retail systems and how the innovation potential of service robots can be harnessed. This research adopts a service system perspective and a three-step approach. After the preliminary study1 is conducted, it explores the drivers of and barriers to the adoption of service robots by customers and FLEs in stationary retail settings. Then, a design science research approach is followed to develop a method for (re-)designing retail systems to effectively incorporate service robots into stationary retail operators. The findings of study 12 and study 23 reveal aspects of both customers’ and FLEs’ acceptance of and resistance to service robots in retail systems. The findings extend prior studies on technology acceptance and resistance, showing i.a. that customers and FLEs have different expectations regarding the use and role of service robots in service environments. While customers perceive service robots as a way to potentially improve the quality of service interactions, FLEs perceive them as leading to deterioration of service interactions. FLEs feel not competent in regard to operating service robots, while customers expect professional, qualified assistance by FLEs. Study 34 integrates the perspectives of customers, FLEs and retail managers to develop a method for (re-)designing retail systems to effectively incorporate service robots into stationary retail operator
Keywords: service robots; service systems; technology acceptance and resistance; retail innovation; design science research; human–robot interaction

Managing Robotics in Retail - A Service Systems Perspective - Meyer, Patrick (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
This book answers the question of how to manage service robots in brick-and-mortar dominated retail service systems to allow for key stakeholders’ adoption and to foster value co-creation. It starts by demonstrating the scientific relevance of the topic as well as deriving a set of promising research questions. After introducing service-dominant logic as a theoretical research lens and elucidating service systems along with their underlying concept of value co-creation as relevant key concepts, five studies are presented. The author´s findings show that understanding and differentiating between consensus, shared and idiosyncratic drivers of and barriers to the adoption of service robots in retail service systems by all key stakeholders, i.e. customers, frontstage employees, and retail managers, is crucial to be able to fully cope with the complexity inherent in the adoption of service robots in service organizations. Moreover, the designed and evaluated artifact fosters a paradigm shift from a one-time technology introduction to a continuous technology management approach including iterations of experimenting, piloting, and implementing.<br
Keywords: Human-computer intercation; service systems; Retailing; Robots; Service robots; Technology adoption; human-robot interaction; artificial intelligence; service innovation

Potentiale von Servicerobotern am Point of Sale - Meyer, Patrick; Roth, Angela; Gutknecht, Klaus; Möslein, Kathrin (Robotik in der Wirtschaftsinformatik, 2023)
Aufgrund steigender Online-Konkurrenz, zunehmenden Kostendrucks und omnikanaler Customer Journeys versucht der stationäre Handel durch den Einsatz innovativer Technologien neue Mehrwerte für Kunden zu bieten. In diesem Zusammenhang wird der Einsatz von Servicerobotern am Point of Sale (POS) ebenso kontrovers wie erwartungsvoll diskutiert, die Akzeptanz der Kunden ist dabei eine entscheidende Voraussetzung. Studienergebnisse zeigen, dass der unmittelbar wahrgenommene Nutzen des Serviceroboters für die langfristige Nutzungsabsicht entscheidend ist. Während sich die wissenschaftliche Forschung bislang überwiegend darauf konzentriert, die Haltung von Kunden und Verkaufsmitarbeitern gegenüber Servicerobotern zu verstehen oder einzelne Anwendungsfälle von Servicerobotern zu validieren, bleibt für einen zielgerichteten Einsatz von Servicerobotern offen, für welche expliziten Tätigkeiten Serviceroboter am POS geeignet erscheinen. Im Rahmen einer explorativen Interviewstudie wurden zwölf Handelsexperten und zwölf Experten aus dem Bereich Servicerobotik zu Einsatzmöglichkeiten von Servicerobotern am Point of Sale befragt. In Anlehnung an die Task-Technology-Fit-Theorie wurden relevante Tätigkeiten und Fähigkeiten von Frontstage-Mitarbeitern mit den gängigen technischen Leistungsmerkmalen von am Markt erhältlichen Servicerobotern abgeglichen und deren Relevanz für das Verkaufsgespräch gewichtet. Die Ergebnisse des Abgleichs wurden entlang der fünf Phasen eines Verkaufsgesprächs strukturiert. Basierend darauf wurden die Erkenntnisse in eine Weboberfläche überführt, welche Wissenschaftler und Praktiker für eine erste schnelle Indikation über die Einsatzmöglichkeiten von Servicerobotern am POS nutzen können.<br

Retail Managers’ Perceptions of Service Robots in Organizational Frontlines – A Mixed Methods Approach - Meyer, Patrick; Nelson, Anja; Schymanietz, Martin (20th Conference of the European Academy of Management (EURAM), 2020)
Due to rising online competition, increasing cost pressure and omnichannel customer journeys, stationary retailers are attempting to co-create value with customers and frontline employees (FLEs) through new technologies. Technological advances are expected to profoundly change stationary retail’s service systems. Among other technologies, service robots are said to have the potential to revitalise interactive value creation in stationary retail. To date, scholarly research has tended to focus on understanding individual stakeholder’s perceptions of service robots in isolation – either focusing on customers’ or FLEs’ acceptance of and resistance to service robots, while leaving the retail managers’ perspective out of consideration. In this study, a mixed methods approach, combining a systematic literature review (SLR) and a qualitative exploratory interview study among 14 retail managers, is adopted to gain a profound and comprehensive understanding of retail managers’ perceptions of service robots in retail systems. While the SLR identified articles that mainly focus on customers’ and/or FLEs’ perceptions of service robots and only address the retail manager’s issues in the managerial implications, the findings of the subsequently conducted interview study identifies nine aspects of acceptance of and resistance to service robots by retail managers, such as distressed workforce, quality of service interaction or impact on company image.</i
Keywords: service robots; retail management; service systems; organizational frontline; technology acceptance and resistance; retail innovation

Service robots in organisational frontlines-A retail managers' perspective - Meyer, Patrick; Roth, Angela; Gutknecht, Klaus (Journal of Retailing and Consumer Services, 2023)
Service robots (SR) have the potential to revitalise value creation in brick-and-mortar retailing. While both the competitive and evolving nature of the retailing industry as well as customers and FLE have obtained substantial coverage in academic literature, the managerial angle towards SR in organisational frontlines has rarely been addressed in service research. This qualitative exploratory interview study explores retail managers' perceptions of SR in organisational frontlines. Building on 28 in-depth interviews with retail managers, three dimensions of predisposing factors (impact on the functional, relational and organisational level), as well as two aggregated dimensions of managerial coping strategies (transforming FLE and work routines) were identified. Further, the findings reveal that retail managers perceive inherent difficulties in balancing the needs of customers and FLE when it comes to effective SR implementation.
Created from Fastlane, WoS look-up

Servitization in Germany – Establishing the context of servitization in manufacturing firms - Kurtz, Julian; Meyer, Patrick; Roth, Angela (Proceedings of the 9th International Conference on Business Servitization (ICBS 2022), 2022)
This book of abstracts summarizes the proceedings of the 9th International Conference on Business Servitization (ICBS 2022), held at Hotel Ilunion, Malaga, Spain. On this edition, the conference places a special emphasis on the focal theme: Servitization as a springboard for enhancing Sustainable manufacturin
Keywords: Servitization; Service Systems; Digital Transformation

Shake Hands with a Robot: Understanding Frontstage Employees’ Adoption of Service Robots in Retailing - Meyer, Patrick; Spreer, Philipp; Gutknecht, Klaus (Marketing Review St. Gallen, 2022)

Structuring the servitization journey – A socio-technical methodology for developing platform-based smart PSS - Kurtz, Julian; Meyer, Patrick; Lugmair, Nina; Roth, Angela (Proceedings of the 10th International Conference on Business Servitization (ICBS 2023), 2023)